3D modeling from using spiral cone-beam trajectory - Narkbuakaew, W.; Withayachumnankul, W.; Pintavirooj, C.; Sangworasil, M. (My University, 2005)
Tomographic imaging is a technique for exploration of a cross-section of an inspected object without destruction. Normally, the input data, known as the projections, are gathered by repeatedly radiating coherent waveform through the object in a number of viewpoints, and receiving by an array of corresponding detector in the opposite position. In this research, as a replacement of radiographs, the series of photographs taken around the opaque object under the ambient light is completely served as the projections. The process is called photographic tomograph. In this paper, we purpose the 3D shape extraction based on using photographic tomography with spiral cone-beam trajectory. We have demonstrated that the purposed technique can rectify the problem of perspective occlusion that occurs when using cone-beam trajectory.
Keywords: 3D rendering; Image reconstruction; Photographic tomography; Spiral cone-beam tomography